Are housing tenure and car access still associated with health? A repeat cross-sectional study of UK adults over a 13-year period - L Macdonald; A Kearns; A Ellaway (BMJ Open)
Background It is usually assumed that housing tenure and car access are associated with health simply because they are acting as markers for social class or income and wealth. However, previous studies conducted in the late 1990s found that these household assets were associated with health independently of social class and income. Here, we set out to examine if this is still the case.Methods We use data from our 2010 postal survey of a random sample of adults (n=2092) in 8 local authority areas in the West of Scotland. Self-reported health measures included limiting longstanding illness (LLSI), general health over the last year and the Hospital Anxiety and Depression Scale.Results We found a statistically significant relationship between housing tenure and all 4 health measures, regardless of the inclusion of social class or income as controls. Compared with owner occupiers, social renters were more likely to report ill-health (controlling for social class—LLSI OR: 3.24, general health OR: 2.82, anxiety η2: 0.031, depression η2: 0.048, controlling for income—LLSI OR: 3.28, general health OR: 2.82, anxiety η2: 0.033, depression η2: 0.057) (p<0.001 for all models). Car ownership was independently associated with depression and anxiety, with non-owners at higher risk of both (controlling for income—anxiety η2: 0.010, depression η2: 0.023, controlling for social class—anxiety η2: 0.013, depression η2: 0.033) (p<0.001 for all models).Conclusions Our results show that housing tenure and car ownership are still associated with health, after taking known correlates (age, sex, social class, income) into account. Further research is required to unpack some of the features of these household assets such as the quality of the dwelling and access to and use of different forms of transport to determine what health benefits or disbenefits they may be associated with in different contexts.